The nanny eaudiobook - Ferguson, Lana (Books on Tape, 2023)
A woman discovers the father of the child she is nannying may be her biggest (Only)Fan in this steamy contemporary romance by Lana Ferguson.   Suddenly unemployed and on the brink of eviction, Cassie Evans is left with two choices: get a new job (and fast) or fire up her long-untouched OnlyFans account. But the job market is terrible, and as for OnlyFans. . . . Well, there are reasons she can’t go back. Just when all hope seems lost, an ad for a live-in nanny position seems like the solution to all her problems. It’s almost too perfect—until she meets her would-be employer.   Aiden Reid, executive chef and DILF extraordinaire, is far from the stuffy single dad Cassie was imagining. He shocks her when he tells her she’s the most qualified applicant he’s met in weeks, practically begging her to take the job. With hands that make her hindbrain howl and eyes that scream sex, the idea of living under the same roof as Aiden feels dangerous, but with no other option, she decides to stay with him and his adorably tenacious daughter, Sophie.   Cassie soon discovers that Aiden is not a stranger at all, but instead someone who is very familiar with her—or at least, her body. Given that he doesn’t remember her, Cassie is faced with what feels like an impossible situation. As their relationship heats to temperatures hotter than any kitchen Aiden has ever worked in, Cassie struggles with telling Aiden the truth, and the more terrifying possibility—losing the best chance at happiness she’s ever had.